Desain meja dan kursi sistem modular berbasis active learning untuk siswa sekolah dasar - Achmad Zainudin; Rahmanu Widayat; Agus Purwantoro (Institut Seni Indonesia Yogyakarta, 2018)
Improve of learning quality of elementary school in Indonesia are many ways. One of them is repairing table-chair as long as growing of learning method. Nowadays, active learning is one of method that improving learning quality. There are many ways in actions to realize active learning, started from curriculum repaired to study time at school. Too poor, the government forgetting one thing, that is table-chair, the product in daily using. This research intend to given argument to all of person or institution about repairing table-chair of elementary school as fit as active learning method by modular concept. Research method in this field is descriptive qualitative. Research location is Kedung District Jepara Regency Central Java, by three sample of class table-chair 6th elementary school in SD Negeri 1 Jondang, MI Matholiul Huda Bugel and SD Negeri III Menganti. The object is design of table-chair elementary school based of active learning. Data collection technique is library study, observation and interview. The data in collection tested in validity by triangulation technic. Research result is showing that table-chair in the data not representative to active learning. Generally, the table-chair is difficult to using in active learning. Table-chair design by modular concept is fit to cluster model/V group and U that ergonomic and functional, so easy to driven and support active learning. Key words: design, elementary school table-chair, active learning, modular concept